Prinsip-prinsip dan Teori-teori belajar dalam Pembelajaran - Fika Aulia Putri; Jefriman Akmal; Gusmaneli Gusmaneli (Jurnal Budi Pekerti Agama Islam, 2024)
Learning is a complex process that involves various factors, including learning principles and theories. Understanding these principles and theories is very important for educators to design and implement effective learning. Understanding learning principles and theories can help educators to create a conducive learning environment, choose appropriate learning strategies, and assess student learning progress. Thus, learning principles and theories are an important foundation for effective learning practices. The method used is the literature method which explores various sources and literacy related to the material.